Designing surveys a guide to decisions and procedures - Blair, Johnny (SAGE, 2014)
Written with the needs and goals of a novice researcher in mind, this fully updated third edition provides an accurate account of how modern survey research is actually conducted. In addition to providing examples of alternative procedures, Designing Surveys shows how classic principles and recent research guide decision-making from setting the basic features of the survey through development, testing, and data collection.